The Effect of Substitution of Wheat Flour with Sorghum Flour (Sorghum bicolor, L) on the Level of Consumer Preference for Cookies - Sondang Dhea Farrah; Esi Emilia; Erli Mutiara; Rasita Purba; Fatma Tresno Ingtyas; Marhamah Marhamah (Universitas Pendidikan Indonesia (UPI), 2023)
Cookies or pastries are food products made from flour that are baked to have a moisture content of less than 5%. Usually the recipe for cookie products is enriched with fat and sugar and added developer ingredients. The use of wheat flour in Indonesia is still increasing, so by utilizing sorghum flour it will be able to help reduce the use of wheat and can help the government in food diversification programs. The main factor that is seen to assess the quality and quality of a product is based on the appearance of the product presented, the aroma, and the taste of the product. The purpose of this study was to analyze the level of consumer preference (color, taste, aroma, texture) through organoleptic tests. The design of this study used experimental research with the RAL method (Completely Randomized Design). Sorghum flour substitution formulations in 4 treatments were control (T0), 50% (T1), 70% (T2), 90% (T3). The research location is at Medan State University with 30 research subjects. Organoleptic test results data were analyzed descriptively using the percentage of consumer acceptance of each cookie formulation and continued with the one-way-Anova test and continued with the DMRT (Duncan) test. The results of this study indicate that the best formula is substitution of 50 percent sorghum flour obtained from the mean value of 4.55 for the control formulation (T0), 4.34 (T1), 3.97 (T2), and 3.70 (T3).